BOUNDEDNESS OF GEOMETRIC INVARIANTS NEAR A SINGULARITY WHICH IS A SUSPENSION OF A SINGULAR CURVE - Martins, Luciana f. [UNESP] (2024)
. Near a singular point of a surface or a curve, geometric invariants diverge in general, and the orders of this divergence, in particular the boundedness about these invariants, represent the geometry of the surface and the curve. In this paper, we study the boundedness and orders of several geometric invariants near a singular point of a surface which is a suspension of a singular curve in the plane, and those of the curves passing through the singular point. We evaluate the orders of the Gaussian and mean curvatures, as well as those of the geodesic and normal curvatures, and the geodesic torsion for the curve.